IMPROVE THE QUAIITY OF ENVIRONMENT AGRICUITURAI EXTENSION SYSTEM THE PROVINCES OF CENTRAL REGLON OF IRAQ - & AL – Mashhadany, AL-raghi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research   aimed  at   explorivg   the  reality  of  environmental   agricultural  extension  system and visualiz  proposal to improve the quality agricultural  extension systemcontaining the environmental  agricltural  extension inputs , operations   outputs  and Continuou improvemen .The research community included the provinces of  the central regionof Iraq  8 Provinces  where the  number of employees 186   respondents  Anbar  and  Salah   Religion   excluded because  of  the    security   conditions at  the time of data  collection, and thus the research  community became  (6)Provinces A random sample of (70%) was take by 4 governorates  Baghdad,Najaf supervision , Karbala ,  Babil) ,due to  the  small   number of   workers   in  the   provinces   covered   by  the  research, a whole community   was   taken of   148  respondents To   achieve  research  objective    questionnaire designed   to  collect   data from  respondents consisted   of   Fenta  scale  including   89 paragraphs   were  distributed  among  four  field , including     28 inputs and  39   operation   ,  and  16   outputs  ,    and    continuous    improvement .  In  order   to  analyze  and   display  the  results  ,  statistical  analysis   software    Spss   was  and  manual  analysis  .  The  search  results  were:  The   reality   of Agricultural  Extension  and  environment  system is weak  through Results Reached  by researcher .The   majority  of  the  respondents   agreed    to   the   proposed    concept    To    improve  the     quality    system   composed    of  agricultural  inputs  ,   processes  ,  outputs , and  continuous  improvement There  are variations in the   importance  of  axes  and  paragraphs  of  environmental  Agricultural  extension  system in the   provinces   of Central  region  of Iraq , but  these  were  minor  variation  which indicates  that  most   of   them   were   important The researcher reached  the  following  recommendations .And the  need  to  form  a joint  committee  between  the ministries   concerned with the  environment and improve the exchange   of  information